Usage of E-Commerce by European Organic Famers: A Comparative Study of Situation in Latvia And in Ireland - Denis VASILIEV (Communications of International Proceedings, 2021)
Organic farming industry is growing across the EU. Nevertheless, smallholders within the industry experience competitive pressure from larger scale convenient agricultural producers. Along with economies of scale, larger convenient farms often benefit from enhanced access to the market, as they collaborate with national scale retail chains. In this respect, organic producers may experience competitive disadvantage. Modern technologies allow direct access to target consumers through application of e-commerce. However, it is not clear how widespread is the use of the tools among organic farmers. In this study it was decided to compare Internet usage for commercial purposes among Latvian and Irish organic farmers. The countries were selected from different parts of Europe, but with a comparable size of organic farming industry, to get an insight in possible differences in e-commerce usage by organic farmers in Western Europe and Baltics.  A sample of 100 organic farmers was selected from each country and internet search was undertaken examining usage of e-commerce tools by selected farmers. Results of present study suggest that e-commerce is much less developed among Latvian organic farmers in comparison to Irish ones. This finding is surprising as the industry development in the former country is much faster than in the latter one. Nevertheless, Latvian organic farmers tend to suffer from fierce competition with large convenient agricultural producers, tend that does not seem to be so explicit in Ireland. Based on findings of present study it is suggested promotion of e-commerce among Latvian farmers to improve their competitive advantage and support the industry.
Keywords: Communications; Competitive Advantage; E-Agriculture; Sustainability.